Wireless Internet Handbook: Technologies, Standards, and Applications - Furht, Borko (CRC Press, 2009)
Wireless applications are definitely the next big thing in communications. Millions of people around the world use the Internet every day - to stay in touch with remote locations, follow the stock market, keep up with the news, check the weather, make travel plans, conduct business, shop, entertain themselves, and learn. The logical next step is the development of the wireless Internet, where cell phones, PDAs, and laptops let us receive and send e-mails, and perform all the activities that we are currently performing over the wireline Internet.